Early clearance vs persistence of de novo donor‐specific antibodies following lung transplantation. Issue 8 (7th July 2017) - Islam, Ana K.; Sinha, Neeraj; DeVos, Jennifer M.; Kaleekal, Thomas S.; Jyothula, Soma S.; Teeter, Larry D.; Nguyen, Duc T. M.; Eagar, Todd N.; Moore, Linda W.; Puppala, Mamta; Wong, Stephen T. C.; Knight, Richard J.; et al.
Abstract: Background: The natural history of de novo donor‐specific antibodies ( dn DSA) after lung transplantation is not well‐described. We sought to determine the incidence and risk factors associated with dn DSA and compare outcomes between recipients with transient (or isolated) vs persistent dn DSA after transplantation. Methods: A single‐center review of all lung transplants from 1/2009‐7/2013. DSAs were tested eight times in the first year and every 4 months thereafter. Outcomes examined included acute rejection and graft failure. Results: Median follow‐up was 18 months (range: 1‐61 months), and 24.6% of 333 first‐time lung‐only transplant recipients developed a dn DSA. Ethnicity, HLA‐DQ mismatches, post‐transplantation platelet transfusion and Lung Allocation Score >60 were associated with dn DSA ( P <.05). Overall graft survival was worse for dn DSA‐positive vs negative recipients ( P =.025). Of 323 recipients with 1‐year follow‐up, 72 (22.2%) developed dn DSA, and in 25 (34.7%), the dn DSA was transient and cleared. Recipients with transient dn DSA were less likely to develop acute rejection than those with persistent dn DSA ( P =.007). Conclusions: Early post‐lung transplantation, dn DSA occurred in 1/4 of recipients, was associated with peri‐transplant risk factors and resulted in decreased survival. Spontaneous clearance of dn DSA, seen in one‐third of recipients, was associated with a lower risk of acute rejection.